2000
DOI: 10.1038/82225
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous immunization: A human vaccine delivery strategy using a patch

Abstract: Transcutaneous immunization, a topical vaccine application, combines the advantages of needle-free delivery while targeting the immunologically rich milieu of the skin. In animal studies, this simple technique induces robust systemic and mucosal antibodies against vaccine antigens. Here, we demonstrate safe application of a patch containing heat-labile enterotoxin (LT, derived from Escherichia coli) to humans, resulting in robust LT-antibody responses. These findings indicate that TCI is feasible for human imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(191 citation statements)
references
References 19 publications
5
183
0
3
Order By: Relevance
“…There is significant interest in developing epicutaneous vaccination because of the potential for self-administration, ease of delivery and stockpiling, and lack of systemic side effects (26,27). This strategy, delivery of a protein Ag after skin hydration or mild abrasion, has been shown to be effective for multiples Ags and provides protective immunity against virus infection (28,29).…”
Section: A Limited Immune-promoting Role For Langerin ϩ Cellsmentioning
confidence: 99%
“…There is significant interest in developing epicutaneous vaccination because of the potential for self-administration, ease of delivery and stockpiling, and lack of systemic side effects (26,27). This strategy, delivery of a protein Ag after skin hydration or mild abrasion, has been shown to be effective for multiples Ags and provides protective immunity against virus infection (28,29).…”
Section: A Limited Immune-promoting Role For Langerin ϩ Cellsmentioning
confidence: 99%
“…Transcutaneous immunization by topical administration of CT to the skin has been demonstrated to induce a systemic antibody response against both itself and co-administered proteins in mice [74], humans [76], sheep, cats and dogs [81]. In mice [75] and humans [76] it was shown that this immunization route also induces a mucosal immune response.…”
Section: Cholera Toxinmentioning
confidence: 99%
“…Using a simple patch/skin-hydration approach, Glenn et al have demonstrated that effective immunity against protein antigens can be elicited by formulating the vaccine with a bacterial toxin. 26,27 Whether or not the hydration technology will influence genetic vaccines remains to be determined. Gene-gun delivery, which requires that the vaccine inoculum be precipitated onto gold beads, was initially thought to be restricted to plasmid vaccines due to formulation issues.…”
Section: Discussionmentioning
confidence: 99%